Characteristics, Release, and Stability (Kinetics and Shelf-life) of Ciprofloxacin HCl-Alginate-Carrageenan Microspheres: Effects of Drug Concentration and Type of Lyoprotectant - Amiruddin; Rahmadi, Mahardian; Hariyadi, Dewi Melani (Science and Technology Indonesia, 2026)
Tuberculosis, an infectious disease caused by the Mycobacterium tuberculosis bacteria, is one of the main causes of death worldwide. Alternative treatments are necessary due to the rising prevalence of medication resistance in Mycobacterium tuberculosis. Fluoroquinolones, such as ciprofloxacin HCl, are among these alternatives and are generally administered orally, but they have limitations. Therefore, pulmonary targeted inhalation delivery systems have been developed. Inhalation of microspheres enables deposition in the lungs at appropriate particle sizes. This study formulates ciprofloxacin HCl microspheres with an optimal ratio and concentration of polymer combination and crosslinker, aiming to determine the effect of drug concentration and lyoprotectant type on characteristics, release, and stability, including degradation kinetics and shelf life. The results showed that the ciprofloxacin HCl-alginate-carrageenan microsphere powder was yellowish-white, with smooth morphology, a yield percentage of 96.08% ± 0.84 – 97.00% ± 0.19, particle sizes below 5 µm, drug loading between 4.57% ± 0.13 – 6.76% ± 0.06, and entrapment efficiency ranging from 79.45% ± 2.53 – 90.80% ± 0.77. The powder had moisture content below 5% and excellent flow properties. Ciprofloxacin HCl release from microspheres at pH 7.4 for 30 hours was 84.55% ± 0.89 – 90.74% ± 0.22, following Korsmeyer-Peppas kinetics based on the Fickian diffusion mechanism. Ciprofloxacin HCl-alginate-carrageenan microspheres were stable and exhibited good shelf life. This study concluded that particle size, drug loading, entrapment efficiency, and drug release are all influenced by drug concentration, while moisture content and flow properties, with adequate shelf life, are influenced by the type of lyoprotectant.